PESTICIDE TOXIN AND ENVIRONMENT: A CASE STUDY OF VEGETABLE GROWERS OF TEHSIL FAISALABAD - Aqeela saghir; Muhammad Khalid Bashir; Saima Sadaf; Muhammad Rafay Muzamil; Ramsha Rashid; Sohaib Usman; Aisha Rani; Noreen Akhter (International Journal of Contemporary Issues in Social Sciences, 2024)
The aim of this study is to analyze the awareness level of vegetables growers regarding residual effects on environment in peri urban areas of tehsil Faisalabad sadder. Chemical use in agriculture is increasing and residues of chemicals are excreting out into the environment which leads to serious environmental conditions. Environmental pollution is very common problem in developing countries such as Pakistan, India which is rising day by day. A sample size of 128 respondents was selected by using online sampling calculator with 95% confidence level and confidence interval 7. Four vegetable-growing villages from two peri-urban union councils in Tehsil Faisalabad were selected purposively and 32 farmers were selected from each village randomly. A pre-tested and well-structured interview schedule was developed for data collection. The results indicated that more than half (56.3%) of the respondents were using sewage water and were more in numbers as compared to freshwater users. A vast majority (85.2%) of the farmers were using pesticides that indicating the farmers’ interest in using pesticides. More than half (57.8%) of the respondents were aware that acid rain affects plants directly and decreases soil quality to reduce yields from agriculture. However, a vast majority (96.1%) of the farmer’s perception was the harmful ingredients for health and environment must not be added during formulation. There is dire need to be started of the campaigns through media regarding awareness of pesticides residues in vegetables having harmful effects on human health. Government and society have to play key role in this spectrum through introduction of organic farming. Besides, one must be followed precautionary measures before consuming these harmful vegetables.